2018
DOI: 10.3390/nu10101402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agaricus bisporus Mushroom Consumption on Gut Health Markers in Healthy Adults

Abstract: Eating Agaricus bisporus mushrooms may impact gut health, because they contain known prebiotics. This study assessed mushroom consumption compared to meat on gastrointestinal tolerance, short chain fatty acid (SCFA) production, laxation, and fecal microbiota. A randomized open-label crossover study was conducted in healthy adults (n = 32) consuming protein-matched amounts of mushrooms or meat twice daily for ten days. Breath hydrogen measures were taken on day one, and gastrointestinal tolerance was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…The SCFA concentrations in feces of pigs fed the FVS diet significantly increased during the growing-finishing phase. Previous studies indicated that the carbohydrate profiles of mushrooms include different types of low-digestible and non-digestible carbohydrates, such as β-glucans, chitin, oligosaccharides and resistant starch, suggesting that they may stimulate the SCFA concentration and impact gut microbial populations [44]. Chitin concentrations in Flammulina velutipes were 7.7%, and was greater than that in the other mushrooms [45].…”
Section: Effects Of Dietary Fvs Inclusion On Scfa Concentration and Smentioning
confidence: 92%
“…The SCFA concentrations in feces of pigs fed the FVS diet significantly increased during the growing-finishing phase. Previous studies indicated that the carbohydrate profiles of mushrooms include different types of low-digestible and non-digestible carbohydrates, such as β-glucans, chitin, oligosaccharides and resistant starch, suggesting that they may stimulate the SCFA concentration and impact gut microbial populations [44]. Chitin concentrations in Flammulina velutipes were 7.7%, and was greater than that in the other mushrooms [45].…”
Section: Effects Of Dietary Fvs Inclusion On Scfa Concentration and Smentioning
confidence: 92%
“…However, we found no association between intake of mushrooms and the numbers of these genera ( Table 3 ). Hess et al also reported that an intervention of mushrooms in healthy adults in the USA increased the abundance of Bacteroidetes and decreased that of Firmicutes [ 46 ]. In our study, however, we found a negative association between intake of mushrooms and the number of Parabacteroides (belong to Bacteroidetes) ( Table 3 ), inconsistent with previous study [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hess et al also reported that an intervention of mushrooms in healthy adults in the USA increased the abundance of Bacteroidetes and decreased that of Firmicutes [ 46 ]. In our study, however, we found a negative association between intake of mushrooms and the number of Parabacteroides (belong to Bacteroidetes) ( Table 3 ), inconsistent with previous study [ 46 ]. We do not know whether this discrepancy is due to differences in ethnicity and region or in the methods of gut microbiota analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatments were generally well-tolerated. The mushroom-rich diet resulted in relatively higher average stool weight and different fecal microbiota composition including a higher abundance of Bacteroidetes and a lower abundance of Firmicutes (Hess, Wang, Gould, & Slavin, 2018). Introduction of probiotics, prebiotics, or synbiotics into the human diet may bal-ance the host intestinal ecosystem by improving gut microbiota integrity and reducing the incidence and severity of metabolic disorders (Markowiak & Slizewska, 2017;Yoo & Kim, 2016).…”
Section: Macrofungi Regulate Gut Microbiotamentioning
confidence: 99%